Asymmetric α‐Allylation of Glycinate with Switched Chemoselectivity Enabled by Customized Bifunctional Pyridoxal Catalysts - Ma, Jiguo; Gao, Bin; Song, Guanshui; Zhang, Ruixin; Wang, Qingfang; Ye, Zi; Chen, Wen‐Wen; Zhao, Baoguo (Angewandte Chemie International Edition, 2022)
Owing to the strong nucleophilicity of the NH2 group, free‐NH2 glycinates react with MBH acetates to usually deliver N‐allylated products even in the absence of catalysts. Without protection of the NH2 group, chiral pyridoxal catalysts bearing an amide side chain at the C3 position of the naphthyl ring switched the chemoselectivity of the glycinates from intrinsic N‐allylation to α‐C allylation. The reaction formed chiral multisubstituted glutamic acid esters as SN2′–SN2′ products in good yields with excellent stereoselectivity (up to 86 % yield, >20 : 1 dr, 97 % ee). As compared to pyridoxal catalysts bearing an amide side arm at the C2 position, the pyridoxals in this study have a bigger catalytic cavity to enable effective activation of larger electrophiles, such as MBH acetates and related intermediates. The reaction is proposed to proceed via a cooperative bifunctional catalysis pathway, which accounts for the high level of diastereo‐ and enantiocontrol of the pyridoxal catalysts. A novel bifunctional chiral pyridoxal derivative 1 with a bigger catalytic cavity than that of previous pyridoxal catalysts promoted direct asymmetric α‐C allylation of NH2‐unprotected glycinates with Morita–Baylis–Hillman acetates. In this way, the chemoselectivity for glycinates was switched from intrinsic N‐allylation to α‐C allylation to produce chiral glutamic acid esters with excellent stereoselectivity (up to >20 : 1 dr and 97 % ee).